Clinical cystoisosporosis associated to porcine cytomegalovirus (PCMV, Suid herpesvirus 2) infection in fattening pigs - Basso, Walter (Parasitol Int, 2017)
Cystoisospora (syn. Isospora) suis is the causative agent of neonatal porcine coccidiosis and one of the main causes of diarrhoea in suckling piglets worldwide. Infection with porcine cytomegalovirus (PCMV, Suid herpesvirus 2) causes inclusion body rhinitis in pigs. In a Swiss pig herd (n = 2 boars, 7 sows, 2 gilts, 18 finishing pigs, 30 fattening pigs, 54 suckling piglets), an outbreak of PCMV infection with high morbidity in all age categories, characterized by fever, anorexia, reduced general condition, respiratory signs and increased piglet mortality, was diagnosed by histopathology and molecular methods. Five fattening pigs (age ~ 17 weeks) additionally showed diarrhoea, not typical for PCMV infections, and one fattener had to be euthanized due to poor condition. Histopathologically, severe fibrinopurulent jejunoileitis with extensive atrophy and fusion of intestinal villi, loss of goblet cells and crypt abscesses associated to C. suis infection were present. In the liver, herpesvirus intranuclear inclusion bodies were observed and PCMV was confirmed by PCR/sequencing. No further infectious causes of diarrhoea (i.e. Rotavirus A; TGEV; PEDV; PCV-2; enterotoxigenic Escherichia coli or Lawsonia intracellularis) were detected in the euthanized fattener. Coproscopically, C. suis oocysts were identified in the faeces from further fatteners with diarrhoea. While C. suis usually produces disease only in suckling piglets, its association with severe intestinal lesions and diarrhoea in ~ 17-week-old fatteners was surprising. It is supposed that the underlying PCMV infection might have contributed to the presentation of clinical cystoisosporosis in fattening pigs. The interaction mechanisms between these two pathogens are unknown.